(NrASSKAZY O FIZIKE I FIZIKAH (B/s - (NkIKOIN(B, (NiSAAK kONSTANTINOWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1986)
(NbIBLIOGR(B.: (NS(B. 156s
Keywords: (NfIZI^ESKAQ NAUKA W sssrs -- (NiSTORIQs